Azerbaycan siyasi tarihinde Fethali Han Hoyski (1875-1920) - Akarslan, Zeynep (My University, 2022)
Bu çalışmada, Azerbaycan tarihinin önemli siyasi aktörlerinden biri olan Fethali Han Hoyski ve onun Azerbaycan’ın 1918-1920 yılları arasındaki bağımsızlık dönemi ve öncesindeki faaliyetleri ele alınmıştır. Hoy Hanı Cafer Kulu Han neslinden olan Fethali Han, Moskova’da hukuk eğitimi almıştır. 1907 yılında açılan II. Rus Devlet Dumasında Azerbaycan’ı temsil etmiş, Rusya’nın toprak reformunu eleştirmiş, Transkafkasya Seyminde bağımsızlık fikrinin önemli bir savunucusu olarak ortaya çıkmış ve Seymin bağımsızlığını ilan etmesinden sonra kısa süreli de olsa Adalet Bakanlığı görevini üstlenmiştir. Azerbaycan’ın bağımsızlığını kazandığı 1918-1920 yılları arasındaki ilk Başbakanı olan Hoyski, göreve kaldığı süre boyunca üç hükümet kurmuş ve Başbakanlık görevinin yanında Dışişleri Bakanlığı da yapmıştır. Bu çalışmanın amacı Fethali Han Hoyski’nin Azerbaycan siyasi tarihindeki yerine ışık tutmaktır.

This study is about one of the important figures in the history of Azerbaijan, Fethali Han Hoyski and his actions before and during the independence period of Azerbaijan between the years 1918-1920. Fethali Khan, a descendant of Khoy Khanate Cafer Kulu Khan, studied law in Moscow. He represented Azerbaijan in the II. Russian State Duma opened in 1907 and criticized the Russia’s land reform. Also, he emerged as an important defender of the idea of the independence in the Transcaucasian Seim and after the declaration of the Seim, he took on the duty of the Ministry of Justice for a short time of period. Hoyski, who was the first Prime Minister of Azerbaijan between 1918-1920 when it gained its independence, during his tenure, he established three governments and served as the Minister of Foreign affairs along with his duty as the Prime Minister. The aim of this study is to shed light on the role of Fethali Khan Hoyski in the political history of Azerbaijan.
Keywords: Azerbaijan; Azerbaycan; bağımsızlık; Fethali Han Hoyski; Fethali Han Hoyski, 1875-1920; History; II. Rus Duması Fethali Han Hoyski; II. Russian Duma; Independence; Tarih; Transcaucasian Seim; Transkafkasya Seymi